1996
DOI: 10.1159/000289069
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eating Disorders in Italy: A Survey on a Sample of 16-Year-Old Female Students

Abstract: Background: To date, the number of epidemiological studies on eating disorders (ED) in Italy and in other Mediterranean countries is still limited. This study evaluated the eating attitudes and the prevalence of eating disorders in a sample of 359 16-year-old Italian schoolgirls. Methods: The study followed a two-stage procedure consisting in a first screening stage followed by clinical interviews. A third stage consisting in a case register study and a 1-year follow-up confirmed the importance of evaluating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
3
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 13 publications
6
48
3
3
Order By: Relevance
“…Past studies which included the adolescent population found higher prevalence for bulimia nervosa than in our study: from 1.1%, in a 15-17 years old Italian sample of school-aged students (Santonastaso et al, 1996), to 1.2% in Sweden (Råstam et al, 1989). However, prevalence similar, or lower than ours, have also been reported in samples including adolescent respondents: from 0.2% among 2544 students aged 13-18 in the USA (Whitaker et al, 1990), to 0.5% in Hong-Kong (N = 1020 students, 17-24 years old) (Lee, 1993).…”
Section: Discussioncontrasting
confidence: 74%
“…Past studies which included the adolescent population found higher prevalence for bulimia nervosa than in our study: from 1.1%, in a 15-17 years old Italian sample of school-aged students (Santonastaso et al, 1996), to 1.2% in Sweden (Råstam et al, 1989). However, prevalence similar, or lower than ours, have also been reported in samples including adolescent respondents: from 0.2% among 2544 students aged 13-18 in the USA (Whitaker et al, 1990), to 0.5% in Hong-Kong (N = 1020 students, 17-24 years old) (Lee, 1993).…”
Section: Discussioncontrasting
confidence: 74%
“…The EAT [13]and the Body Attitudes Test (BAT) [14]were administered as self-reported questionnaires. The Italian versions of these scales have been validated and used in previous studies [15, 16]. About one third of the models (35%) preferred to complete the questionnaires in the Italian version.…”
Section: Methodsmentioning
confidence: 99%
“…The first group consisted of 10 randomly selected classes while the control group was made up of students randomly selected from those not participating in the program. Part of the sample (two schools) also took part in a two-stage epidemiological study [21]. …”
Section: Methodsmentioning
confidence: 99%